f ( x ) = x 5 a + 1
Function f ( x ) is defined as above, where a = n → − 2 lim n 3 + 3 n 2 + n − 2 2 ( n 3 − 2 n + 4 ) .
If d x 1 0 0 d 1 0 0 f ( x ) = y ! at x = 1 , find y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This might sound like nit picky hair splitting from me but I think the derivative should look more like 1 0 1 ! x , and only when it is evaluated at x = 1 do you obtain 1 0 1 ! . If for example, you evaluated the 1 0 1 s t derivative at x = 1 0 2 , then the answer would have been y = 1 0 2 .
Problem Loading...
Note Loading...
Set Loading...
for a = n → − 2 l im n 3 + 3 n 2 + n − 2 2 ( n 3 − 2 n + 4 )
Factorizing we get, a = n → − 2 l im ( n 2 + n − 1 ) ( n + 2 ) 2 ( n 2 − 2 n + 2 ) ( n + 2 )
Thus a = ( n 2 + n − 1 ) 2 ( n 2 − 2 n + 2 ) a t n = − 2
a = 20
d x 1 0 0 d 1 0 0 ( x 1 0 1 ) = 1 0 1 !
y = 1 0 1